Analisis Kualitas, Desain, Dan Harga Terhadap Keputusan Pembelian Sepatu Olahraga Produk NIKE Melalui Gaya Hidup Sebagai Variabel Intervening Di Kabupaten Sidoarjo - Muhammad Rifqi Achmadi; Supardi Supardi; Sriyono Sriyono; Wisnu Panggah Setiyono (Acman: Accounting and Management Journal, 2022)
The purpose of this study is to conduct a Quality, Design and Price Analysis of the Purchasing Decision of Nike Sports Shoes Through Lifestyle as an Intervening Variable in Sidoarjo Regency. The research on Quality, Design and Price Analysis of the Decision to Purchase Nike Sports Shoes Products Through Lifestyle as an Intervening Variable in Sidoarjo Regency is to use quantitative methods in the form of surveys assisted by questionnaires and by using secondary data to become comparative materials. The sample used was 200 people who were determined by the purposive sample method in this case were users of Nike sports shoes with varying age ranges ranging from less than 20 years of age to 40 years. The analytical tools used are multiple linear regression test analysis, coefficient of determination (R2), correlation coefficient, and t test using the SPSS version 24 program. The result of this study is that product quality has a significant effect on purchasing decisions. Product design has a significant effect on sales decisions. The price of the product has an insignificant effect on sales decisions. Product quality through lifestyle does not have a significant effect on purchasing decisions. Product design through lifestyle has no significant effect on purchasing decisions. The price of products through lifestyle has a significant effect on purchasing decisions.